2016
DOI: 10.1007/s11302-016-9497-4
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptors induce degranulation in human mast cells

Abstract: Mast cells play important roles in host defence against pathogens, as well as being a key effector cell in diseases with an allergic basis such as asthma and an increasing list of other chronic inflammatory conditions. Mast cells initiate immune responses through the release of newly synthesised eicosanoids and the secretion of pre-formed mediators such as histamine which they store in specialised granules. Calcium plays a key role in regulating both the synthesis and secretion of mast-cell-derived mediators, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(57 citation statements)
references
References 46 publications
10
47
0
Order By: Relevance
“…These results support the idea that ATP mobilization during MS occurs at least in part via P2X 7 R activation, along with P2Y 13 R, and added to accumulating evidences of P2X 7 R‐mediated ATP regeneration [23,47,48] . Regarding MCs, P2X 7 R was indicated to contribute to the degranulation of mouse bone marrow‐derived MCs, [46] LAD 2 human MCs line [49] and MCs in the colons of mice [50] …”
Section: Discussionsupporting
confidence: 81%
“…These results support the idea that ATP mobilization during MS occurs at least in part via P2X 7 R activation, along with P2Y 13 R, and added to accumulating evidences of P2X 7 R‐mediated ATP regeneration [23,47,48] . Regarding MCs, P2X 7 R was indicated to contribute to the degranulation of mouse bone marrow‐derived MCs, [46] LAD 2 human MCs line [49] and MCs in the colons of mice [50] …”
Section: Discussionsupporting
confidence: 81%
“…; Wareham et al. ; Wareham and Seward ); therefore, demonstrating that this level of mRNA expression could be sufficient to provide a functional contribution to cell physiology.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, TRPM7 (<0.4) and P2X7 (<2 -data not shown) were detected at similar levels to the TRPC family subtypes. Both these channels have previously been functionally characterized in human mast cells (Wykes et al 2007;Wareham et al 2009;Wareham and Seward 2016); therefore, demonstrating that this level of mRNA expression could be sufficient to provide a functional contribution to cell physiology. In order to verify the consistency of expression of TRPC subtypes in HLMCs between different lung donors, qPCR was performed on four additional lung donors.…”
Section: Trpc1 and 6 Are Expressed In Lad2 And Hlmcsmentioning
confidence: 99%
“…286 A recent study also showed that P2X7 is responsible for high concentration of ATP-mediated MC degranulation in LAD2 human MCs. 287 Notably, P2X7 is highly expressed by ex vivo cultured human MCs (HMC-1 and activated CBMC), but no detection of this receptor was found in human primary MCs isolated from lung and skin. 284 ATP levels are significantly elevated in the airways of asthmatic patients after allergen challenge and in mice in a model of ovalbumin (OVA)-induced asthma.…”
Section: Purinergic Receptorsmentioning
confidence: 99%
“…ATP‐mediated activation of P2X7 induces the production of inflammatory cytokines (IL‐6, TNF‐α, and oncostatin M), chemokines (CCL2, CCL7, and CXCL2), and leukotrienes from MCs, which subsequently exacerbate intestinal inflammation . A recent study also showed that P2X7 is responsible for high concentration of ATP‐mediated MC degranulation in LAD2 human MCs . Notably, P2X7 is highly expressed by ex vivo cultured human MCs (HMC‐1 and activated CBMC), but no detection of this receptor was found in human primary MCs isolated from lung and skin …”
Section: Alarmin Receptorsmentioning
confidence: 99%